2020
DOI: 10.48550/arxiv.2003.11974
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Topological Characterization of Modulo-$p$ Arguments and Implications for Necklace Splitting

Abstract: The classes PPA-p have attracted attention lately, because they are the main candidates for capturing the complexity of Necklace Splitting with p thieves, for prime p. However, these classes are not known to have complete problems of a topological nature, which impedes any progress towards settling the complexity of the problem. On the contrary, such problems have been pivotal in obtaining completeness results for PPAD and PPA, for several important problems, such as finding a Nash equilibrium [Daskalakis et a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Beyond equilibrium computation and its applications to Economics and Game Theory, the study of total search problems has found profound connections to many scientific fields, including continuous optimization [DP11,DTZ18], combinatorial optimization [SY91], query complexity [BCE + 95], topology [GH19], topological combinatorics and social choice theory [FG18,FG19,FRHSZ20b,FRHSZ20a], algebraic combinatorics [BIQ + 17, GKSZ19], and cryptography [Jeř16,BPR15,SZZ18]. For a more extensive overview of total search problems we refer the reader to the recent survey by Daskalakis [Das18].…”
Section: Further Related Workmentioning
confidence: 99%
“…Beyond equilibrium computation and its applications to Economics and Game Theory, the study of total search problems has found profound connections to many scientific fields, including continuous optimization [DP11,DTZ18], combinatorial optimization [SY91], query complexity [BCE + 95], topology [GH19], topological combinatorics and social choice theory [FG18,FG19,FRHSZ20b,FRHSZ20a], algebraic combinatorics [BIQ + 17, GKSZ19], and cryptography [Jeř16,BPR15,SZZ18]. For a more extensive overview of total search problems we refer the reader to the recent survey by Daskalakis [Das18].…”
Section: Further Related Workmentioning
confidence: 99%